Pengaruh Media Sosial Instagram dan Brand Awareness Terhadap Keputusan Pembelian di Grafika Cikole Lembang - Wova Oktavia; Nova Riana; Erie Hidayat (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
This research aims to determine; (1) Grafika Cikole on social media Instagram, (2) brand awareness of Grafika Cikole, (3) tourist purchase decisions in Grafika Cikole, (4) the influence of social media Instagram and brand awareness on tourist purchasing decisions in in Grafika Cikole Lembang. This research is included in quantitative research with descriptive and verificative analysis whose information is collected from respondents using questionnaires and interview with informants. The population of this research is the entire tourist of Grafika Cikole. The sampling technique used random sampling of 100 respondents. Data collection techniques use questionnaires that has been tested for validity, reliability, and normality. The results of the research at the 5% significance level showed that; social media Instagram positively affects the purchasing decisions of tourists in Grafika Cikole Lembang. This is evidenced by a calculated t value is greater than the table t (4.391 > 1.984), and a significance value of 0.000 < 0.05;brand awareness positively affects the purchasing decisions of tourists in Grafika Cikole Lembang. This is evidenced by a calculated t value is greater than the table t (5.271 > 1.984), and a significance value of 0.000 < 0.05; social media Instagram and brand awareness have a positive influence on the purchasing decisions of tourists in Grafika Cikole Lembang. This is evidenced by the F value calculated > F table (52.907 > 3.09) and the significance value 0.000 < 0.05. The results of this study show that there is a positive and significant influence between Instagram social media and brand awareness on purchasing decisions by 52.2%.